Physiological and performance adaptations to varying rest distributions during short sprint interval training trials in female volleyball players: a comparative analysis of interindividual variability - Tao, T.; Zhang, N.; Yu, D.; Sheykhlouvand, M. (International Journal of Sports Physiology and Performance, 2024)
Purpose This study aimed to examine the impact of different rest periods between short sprint interval training (SSIT) trials on the physiological and performance adaptations of female volleyball players.